Minimizing the Makespan for Unrelated Parallel Machines - GUO, Yunsong (Institutional Knowledge at Singapore Management University, 2007)
In this paper, we study the unrelated parallel machine problem for minimizing the makespan, which is NP-hard. We used Simulated Annealing (SA) and Tabu Search (TS) with Neighborhood Search (NS) based on the structure of the problem. We also used a modified SA algorithm, which gives better results than the traditional SA and developed an effective heuristic for the problem: Squeaky Wheel Optimization (SWO) hybrid with TS. Experimental results average 2.52% from the lower bound and are within acceptable timescales improving current best results for the problem.